The laws of learning from the perspective of Islamic psychology - Al'Mahdi, Muhammad, Dr.; Saba Islamic Media (Kuala Lumpur : Saba Islamic Media, 2004)
This program contain a brief and simplified overview of a complete set of laws of which explain how all learned human development take place
Presenter: Dr. Muhammad Al'Mahdi
Keywords: Islam